The Effectiveness Of Counseling With Cognitive Restructuringtechnique To Improve The Coping Stress Of Cancer Patients (Jurnal Bimbingan Konseling, 2020)
Cancer patients are susceptible to physical and psychological problems that result in immune reduction, and depression showed by the feelings of sad, hopeless, failure, dissatisfaction, worse, having low opinion on their body, and feeling close to death. Therefore, this study intended to examine the effectiveness of counseling with Cognitive Restructuring (CR) technique to improve the coping stress of cancer patients. It used Single Subject Design (SSD) with multiple baseline individual pattern. There were eleven observational sessions in this study, namely three sessions of baseline A1, five sessions of intervention, and three sessions of baseline A2. The overall data of coping stress were collected using guidelines from GAS (Goal Attainment Scaling). Further, graph visual analysis was made to obtain mean, data level, rapidity behavior changes, trend of data changes, level stability, and data overlap. After that, the data went through the calculation of t score and z score. The results showed that the counseling with Cognitive Restructuring (CR) technique was able to improve coping stress.